Are the effects of market concentration and income diversification on banking performance persistent? (2020)
We analyze the effects of market concentration and income diversification on banking performance. We used a sample of 134 countries for the period 1994-2011 and used the GMM estimator proposed by Arellano and Bover (1995). Our results show that market concentration and income diversification have a positive and non-linear effect on bank performance. The non-linearity suggests that the positive effect is reversed if the banking industry has high levels of market concentration and income diversification. During an economic crisis, the banking industry reduces diversification to support its performance. These results are relevant for the design of financial policy and banking strategies.